2017
DOI: 10.24017/science.2017.3.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reinforcement material on impact properties of epoxy

Abstract: Impact characteristics of Epoxy matrix composites is investigated by impact machine. Four different types of reinforcement are used in the experimental works: type one: 1.9wt% steel fiber, 1.9wt% carbon fiber,1.9 wt% carbon nanotube, 1.9 wt% woven carbon fiber. This work shows that reinforcing epoxy with (1.9 wt% of woven carbon fiber) improves the impact properties where energy, force and deformation values of impact test for this composite were 18.4J, 3580.59 N and 18 mm respectively while for epoxy were 2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Ulven et al [26] concluded that, due to the small variation in the ballistic limit and crack propagation, the penetration of carbon/epoxy panels by projectiles with various geometries is significantly dependent on the thickness of the panels. Fadhil et al compared the low velocity impact response of epoxy composites with various reinforcement materials [27]. They reported that the impact force, the deformation of the composites and the impact energy were different for the various types of carbon reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Ulven et al [26] concluded that, due to the small variation in the ballistic limit and crack propagation, the penetration of carbon/epoxy panels by projectiles with various geometries is significantly dependent on the thickness of the panels. Fadhil et al compared the low velocity impact response of epoxy composites with various reinforcement materials [27]. They reported that the impact force, the deformation of the composites and the impact energy were different for the various types of carbon reinforcement.…”
Section: Introductionmentioning
confidence: 99%